IS SOCIOECONOMIC OR RELIGIOUS SIMILARITY MORE DOMINANT IN RESIDENTIAL SEGREGATION IN JAKARTA? A SPATIAL AGENT-BASED MODELING AND SIMULATION APPROACH - Kusumah, Hendra
This study analyses whether religion or socioeconomic status similarity is more dominant in shaping segregation patterns. As a case study, we analyze the segregation patterns of Jakarta – Indonesia, one of the largest global metropolitans. To do so, we use agent-based modeling and extend Schelling's segregation model by incorporating the random utility discrete approach to simulate the inhabitants' relocation decisions. Using actual census data from 2010-2013 and the Jakarta GIS map, we simulate the relocation movements of inhabitants at the sub-district level. We set the inhabitants’ socioeconomic and religious similarities as the independent variables and the housing constraint as the moderating variable. As the dependent variables, we simulate and analyze the segregation indicators (i.e., dissimilarity and Simpson indexes) and spatial indicators (i.e., Moran index and segregation pattern maps). This study concludes that religious similarity is a more dominant determinant compared to the socioeconomic similarity in driving inhabitants’ relocation decisions which leads to segregation patterns. Understanding the collective reasons behind residential segregation is valuable for policymakers in developing a socially sustainable city.